EKSPLORASI IN SILICO SENYAWA BIOAKTIF Sargassum polycystum SEBAGAI KANDIDAT ANTIINFLAMASI UNTUK PAKAN TAMBAHAN IKAN BUDIDAYA - Ni Luh Putu Kayika Febryanti; Ni Pande Made Suartiningsih (JURNAL BIOSENSE, 2026)
Inflammation in cultured fish can reduce health status and productivity, highlighting the need for safe and sustainable natural functional feed additives. This study aimed to explore the potential of bioactive compounds from Sargassum polycystum as anti-inflammatory candidates through an in silico approach targeting cyclooxygenase-2 (COX-2). A total of 16 ligands derived from S. polycystum were obtained from the PubChem database, optimized, and docked against the COX-2 protein using AutoDock v4.2, followed by 2D visualization of ligand–protein interactions. The results showed that the binding energies ranged from -10.2 to -1.83 kcal/mol. Cholest-5-en-3-ol (3β)- exhibited the best binding affinity with a binding energy of -10.2 kcal/mol, followed by Heneicosane, 11-cyclopentyl (-9.0 kcal/mol) and 1,2-benzenedicarboxylic acid (-8.73 kcal/mol). The 2D interaction analysis revealed that Cholest-5-en-3-ol (3β)- formed hydrophobic interactions, hydrogen bonds, and electrostatic interactions within the active pocket of COX-2, and occupied a binding region relatively similar to celecoxib as the reference ligand. These findings suggest that bioactive compounds from S. polycystum have potential as natural anti-inflammatory agents and as candidates for functional feed additives to support fish health in aquaculture, although further computational and experimental validation is still required.